Diagonal strategies : Berger + Parkkinen Architekten - Sarnitz, August; Barrachina Pastor, Francisco, 1977-; Berger, Alfred, 1961-; Parkkinen, Tiina, 1965- (Birkhäuser Verlag, 2017)
The much noted international architects? practice, Berger + Parkkinen, was founded in 1995 by Alfred Berger and Tiina Parkkinen, with practices in Vienna and Helsinki. The practice has worked on a wide variety of projects, including a private medical university, and a timber residential building (together with querkraft Architects). 0The designs produced by Berger + Parkkinen are characterized by an uncluttered, elegant urbanity, as well as by an innovative use of materials. The Nordic Embassies in Berlin (1996?1999), for which the practice has received many awards, are some of their most published projects. 0This first monograph in the form of a bibliophilic, handy book comprises the documentation of about 15 projects, a register of the complete oeuvre, as well as an introductory essay.